2014
DOI: 10.1002/wnan.1282
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle approaches against bacterial infections

Abstract: Despite the wide success of antibiotics, the treatment of bacterial infection still faces significant challenges, particularly the emergence of antibiotic resistance. As a result, nanoparticle drug delivery platforms including liposomes, polymeric nanoparticles, dendrimers, and various inorganic nanoparticles have been increasingly exploited to enhance the therapeutic effectiveness of existing antibiotics. This review focuses on areas where nanoparticle approaches hold significant potential to advance the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
170
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(177 citation statements)
references
References 168 publications
(256 reference statements)
0
170
0
7
Order By: Relevance
“…Passive targeting is based on particle size and the ability of PNPs to form pores, which disrupt the structure of the pathogen membrane [23,36,37]. Recent studies indicate that conjugation of lectin-specific ligands on the PNP surface showed enhanced binding affinity to the carbohydrate receptors on the Helicobacter pylori membrane [38].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive targeting is based on particle size and the ability of PNPs to form pores, which disrupt the structure of the pathogen membrane [23,36,37]. Recent studies indicate that conjugation of lectin-specific ligands on the PNP surface showed enhanced binding affinity to the carbohydrate receptors on the Helicobacter pylori membrane [38].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In another study Jain et al used concanavalin-A (Con-A) decorated elastin as a clarithromycin delivery system for H. pylori eradication [39]. In active targeting other homing molecules including specific antibodies and aptamer bacteriophage proteins have been used for nanoparticle surface functionalization resulting in targeted delivery platforms effective against different types of bacterial infections [37,40,41]. Targeting molecules can also be used for sensitive and specific identification strategies for detection of pathogens such as Staphylococcus aureus, Mycobacterium tuberculosis and Escherichia coli via aptamer recognition and fluorescently tagged silica nanoparticles [42][43][44].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Thus, liposomes are promising delivery systems mainly because of their biocompatibility, biodegradability and low toxicity in the human body (Benech et al 2002;Saddi et al 2008;Shehata et al 2008;Akbarzadeh et al 2013;Gao et al 2014). Any compound, irrespective of its solubility, can be entrapped inside a liposome, resulting in a slow degradation during transport to the target, minimal side-effects and greater stability (Ghalandarlaki et al 2014).…”
Section: Liposomal Systems As Carriers For Bioactive Compoundsmentioning
confidence: 99%
“…In particular novel approaches that can replace or enhance current antimicrobials are highly desired. [3][4][5] Polymeric materials have often been postulated as alternatives in these areas, either as delivery vehicles for antimicrobials, 6,7 or as novel antimicrobial polymers, [8][9][10][11] and materials that can interfere with microbial adhesion. [12][13][14][15] Polymeric materials are especially attractive in these applications because of their multivalency, ease of manufacturing and the potential to precisely control polymer length and composition.…”
Section: Introductionmentioning
confidence: 99%